Sosialisasi Demam Berdarah Dan Praktek Pembuatan Ovitrap Sederhana Di Kelurahan Bandarharjo Semarang - Aerrosa Murenda Mayadilanuari; Silvia Nurvita; Siti Noor Chotimah; Dody Indra Sumantiawan; Viny Natalia Dewi; Meita Fransiska Dara Antidi; Aldi Rizki Yudistira (Lembaga Pengembangan Kinerja Dosen, 2024)
Dengue Hemorrhagic Fever (DHF) remains a serious health issue in Semarang City, particularly in Bandarharjo Sub-district. In an effort to address this problem, a community service activity titled